An Analysis of Modalities of the Book “How Children Succeed” by Paul Tough - Gunawati Gho; Arsen Nahum Pasaribu (Institut Agama Islam Negeri Palopo, 2021)
The study of education book contents has grown in numbers in the last decades. However, the research on the use of modality in the content book is relatively unexplored. Therefore, this research aimed to analyze the content of the book “How Children Succeed” by Paul Tough to find out the types and degree of modalities used. It also shows the most appeared modal used in each chapter and in the book itself. This research was conducted by using the theory of modality by Halliday (2014) in the Systemic Functional Linguistics. The process of data analysis was manually applied without the help of software. Researcher’s concern is how the book is being presented in the area of semantic by the choice of modalities made by the author. The study reveals that the 4 types of modalities are being used which are the probability, usuality, obligation and inclination with all the three degrees of values appeared except for the low degree of inclination. It also revealed the degree of confidence of the author by the choices of modal used in the book. The implication of this study is the book author should pay more attention to the aspect of modality in the education books they write.